2022
DOI: 10.25071/2291-5796.126
|View full text |Cite
|
Sign up to set email alerts
|

Critical Posthuman Nursing Care

Abstract: Nursing care is an embodied and co-creative world-building practice made hypervisible in pandemic times. A traditional praxis that became a professionalized care practice, nursing bares the indelible mark of the ideologies that have come to shape the discipline like whiteness, patriarchy, and capitalism to name a few. Embracing a critical feminist posthuman and new materialist perspective, in this paper we advance the notion that nursing care is a situated and embodied endeavor that cannot and should not be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Who gets to be counted as ‘average’ and ‘neutral’, ‘unmarked’ in Western science has been proven to be a political question, with said average often being equated with white, European, male, property‐owning, speaking a standard language, able‐bodied subject (Braidotti, 2013). This ‘Vitruvian Man’ as the embodiment of standard subject has been reified in medicine as well (Hopkins Walsh et al, 2022; Smith et al, 2022).…”
Section: Biopower Governmentality and Algorithmic Life Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Who gets to be counted as ‘average’ and ‘neutral’, ‘unmarked’ in Western science has been proven to be a political question, with said average often being equated with white, European, male, property‐owning, speaking a standard language, able‐bodied subject (Braidotti, 2013). This ‘Vitruvian Man’ as the embodiment of standard subject has been reified in medicine as well (Hopkins Walsh et al, 2022; Smith et al, 2022).…”
Section: Biopower Governmentality and Algorithmic Life Managementmentioning
confidence: 99%
“…This 'Vitruvian Man' as the embodiment of standard subject has been reified in medicine as well (Hopkins Walsh et al, 2022;Smith et al, 2022). Furthermore, analysis of algorithmic systems and their design has shown that similar issues of centreing the 'average man'-white prototypicality, gender and age insensitivity, eurocentrism, able-and cis-centredness, to mention a few (Benjamin, 2019;Buolamwini & Gebru, 2018;Gebru, 2020;Hutchinson et al, 2019;Keyes, 2018;Leavy, 2018).…”
Section: Biopower Governmentality and Algorithmic Life Managementmentioning
confidence: 99%
“…Explorations of the Vitruvian Nurse illustrate the relevance of critically examining how nursing is imagined because these ideations shape policies, work practices, and healthcare outcomes. The stakes are high when it comes to living and working as a nurse, as the policies that guide nursing arise from western science and philosophy, produce what it is to be human (Haraway, 2016), and reproduce narrow definitions of who and what is allowed to be human (Da Silva, 2007; Hopkins‐Walsh et al, 2022; Jackson, 2020; Yusoff, 2018).…”
Section: The Vitruvian Manmentioning
confidence: 99%
“…The role of nursing has become increasingly professionalized beginning in the 19th century and throughout the 20th century when the discipline entered university as an academic subject. As nursing is not secluded from the societies it developed in, these processes have cocreated a model of nursing that (re)produces inherently misogynistic tropes and reproduces restrictive power relations (Ashley, 1976; Hopkins‐Walsh et al, 2022). The Vitruvian Man is re/created and re/inscribed in the regulatory structures for nurses.…”
Section: The Vitruvian Nursementioning
confidence: 99%
See 1 more Smart Citation